The Adaptation and Cooperation of Minority Muslims in Russian History - Fachrizal A. Halim (Al-Jami'ah: Journal of Islamic Studies, 2013)
The present essay examines the common approach in reading the relationship between Muslims and Russian society as if they were bound by perpetual conflict. Following this angle, historians argue that the Russians underwent long term conflict with Muslims and claim that the Russians have suffered more than any other people in facing the hostile world of Islam. Some also argue that Muslims were completely subdued by the Russians due to Islam’s incompatibility with the secular and atheist Soviet regime. A careful survey of literature on the history of Muslims in Russia, however, does not always lead to the conclusion that the two sides were in continuous conflict. In fact, aside from conflict and subjugation, both Russians and the Muslims enjoyed a considerable level of peace and shared a similar attitude of flexibility in mutual cooperation. Given the extent of flexibility of Muslims in their encounter with the Russians throughout the Czar and the Soviet regimes, I argue that contemporary scholars have scaled down the dynamic of both Russian and Muslims intellectual articulations in relation to modern politics as well as to the internal relationship between the two sides, and that the relationship between them can be written as other than perpetual conflict.[Artikel ini mengulas hubungan Islam dan Rusia yang kerap dijelaskan dalam konteks relasi saling bertentangan. Dari cara pandang demikian, ahli sejarah kerap berpendapat bahwa konflik antara keduanya sudah terjadi lama dan orang Rusia adalah korban paling parah yang diakibatkan kebrutalan Islam. Semantara itu, ahli sejarah lainnya berpendapat bahwa orang Islam sepenuhnya terjajah oleh kekuasaan Rusia karena Islam tidak cocok dengan sistem sekuler dan ateis Soviet. Jika dibaca literatur mengenai sejarah Islam di Rusia, maka relasi konfliktual antara keduanya tidak sepenuhnya benar. Faktanya, terlepas dari konflik dan penaklukan, baik orang Rusia dan umat Islam dapat hidup secara damai dan fleksibel dalam kehidupan sosial mereka. Dengan menjelaskan fleksibelitas relasi antara Muslim dan Rusia pada masa kerajaan Rusia dan rejim Soviet, penulis berargumen bahwa kebanyakan ilmuwan kontemporer menyederhanakan relasi Islam dan Rusia dalam konteks politik modern serta relasi internal antara keduanya, karenanya relasi Islam dan Rusia perlu dijelaskan secara seimbang bahwa relasi konflik antara Islam dan Rusia tidak sepenuhnya benar.]